Analisis Dampak Covid-19 terhadap Kinerja Perbankan - Aditya Iswara; Junaedi (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2022)
This study aimed to analyze the impact of the Corona Virus Disease-19 (Covid-19) pandemic on the performance of PT. Bank Pembangunan Daerah Jawa Timur Tbk. Cabang Magetan, and analyzed the scheme design which contains the most neededstrategic steps to correct the weakening of its performance. The method used in this research is descriptive statistics. The data used are financial statements in financial ratios, including BOPO, NIM, NPL, and CKPN. This study indicates that there has been a change and a slowdown in the financial performance of PT. Bank Pembangunan Daerah Jawa Timur Tbk. Cabang Magetan, both in terms of CKPN, NPL, BOPO, and NIM. Meanwhile, the policy that has been taken to correct these weaknesses is the implementation of a stress test preparation for the fixed effects industry level with the estimation of the ordinary least square model and the balance sheet approach, which can capture the dynamics of individual banks in surviving the shocks given in the stress test scenario (PD, LGD, and EAD) to see industrial resilience. Keywords: Covid-19; Banking; Financial Performance